Validity and reliability of the 'Ten Questions' questionnaire for detecting moderate to severe neurological impairment in children aged 6-9 years in rural Kenya. - Mung'ala-Odera, V; Meehan, R; Njuguna, P; Mturi, N; Alcock, K; Carter, J; Newton, C (2004)
BACKGROUND: The 'Ten Questions' Questionnaire (TQQ) is used to detect severe neurological impairment in children living in resource-poor countries. Its usefulness has been established in Asia and the Caribbean, but there are a few published studies from Africa. We evaluated the TQQ as part of a larger study of neurological impairment in a rural community, on the coast of Kenya. METHODS: The study was conducted in two phases from June 2001 to May 2002; in phase one, a community household screening of 10,218 children aged 6-9 years using the TQQ was performed. Phase two involved a comprehensive clinical and psychological assessment of all children testing positive on the TQQ (n = 810) and an equivalent number of those testing negative (n = 766). Data were interpreted using the impairment-specific approach. RESULTS: Overall, the sensitivity rates for screening the different impairments were: cognitive (70.0%), motor (71.4%), epilepsy (100%), hearing (87.4%) and visual (77.8%). All the specificity rates were greater than 96%. However, the positive predictive values were low, and ranged from 11 to 33%. CONCLUSIONS: These results are similar to those from other continents and provide evidence that the TQQ can be used to compare the epidemiology of moderate/severe impairment in different parts of the world. Furthermore, the TQQ can be used to screen for moderately/severely impaired children in resource-poor countries; however, the low positive predictive values mean that other assessments are required for confirmation.